2021
DOI: 10.18502/cmm.6.4.5327
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of asymptomatic nosocomial candiduria due to Candida glabrata among hospitalized patients with heart failure: a matter of some concern?

Abstract: Background and Purpose: Heart failure is a leading cause of hospitalization, and asymptomatic candiduria is common in hospitalized patients with low morbidity. However, in most patients, it is resolved spontaneously on the removal of the catheter. Despite the publication of guidelines, there are still controversies over the diagnosis and management of candiduria. However, in hospitalized patients with heart failure, the decision to treat candiduria is especially important since the nosocomial infections are as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…In a clinical study in-hospital mortality was 48.8% in patients with candiduria compared to 36.6% in those without candiduria ( p <0.001), they also found significant differences for ICU mortality (38.% vs. 28.1%, p <0.001).8 Researchers found, candiduria detected at any time in the surgical ICU was independently associated with mortality. 24 Our study also revealed candiduria as an independent risk factor for mortality ( p <0.001). The incidence of concurrent candidemia is infrequent and has been encountered in 1-8% of patients with candiduria, even so, ICU patients constitute the high-risk group.…”
Section: Discussionsupporting
confidence: 68%
“…In a clinical study in-hospital mortality was 48.8% in patients with candiduria compared to 36.6% in those without candiduria ( p <0.001), they also found significant differences for ICU mortality (38.% vs. 28.1%, p <0.001).8 Researchers found, candiduria detected at any time in the surgical ICU was independently associated with mortality. 24 Our study also revealed candiduria as an independent risk factor for mortality ( p <0.001). The incidence of concurrent candidemia is infrequent and has been encountered in 1-8% of patients with candiduria, even so, ICU patients constitute the high-risk group.…”
Section: Discussionsupporting
confidence: 68%
“…Invasive candidiasis, which is often associated with hospitalization, involves blood infections (candidemia) and serious infections such as intra-abdominal abscesses, peritonitis and osteomyelitis [39], pneumonia [40], ocular candidiasis [26], endocarditis [41], candiduria [42], and fungal infection in the central nervous system [43]. Almost all organs can become secondarily infected after hematogenous dissemination of the fungus [19].…”
Section: Systemic Candidiasismentioning
confidence: 99%
“…Patients with acute candidemia are considered if there is evidence of involvement of multiple non-contiguous organs. The colonization and infection of the urinary system is another possible indication of candidemia when the agent is isolated in urine culture [ 40 42 ]. Other possible clinical manifestations in fungemia include pyelonephritis, peritonitis, arthritis, hepatosplenic abscesses, myositis, macronodular lesions in the dermis, endophthalmitis, meningitis, and generalized systemic involvement [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%